Palaeoecology of Sphagnum riparium (Ångström) in Northern Hemisphere peatlands: Implications for peatland conservation and palaeoecological research - Gałka, Mariusz; Galloway, Jennifer M; Lemonis, Natalie; Mazei, Yuri A; Mitchell, Edward A.D; Morse, Peter D; Patterson, Timothy R; Tsyganov, Andrey N; Wolfe, Stephen A; Swindles, Graeme T (2018)
Sphagnum riparium (Ångström) is a rare constituent of modern peatland plant communities and is also very rarely found as a subfossil in peat archives. We present new data on the occurrence of Sphagnum riparium macrofossils in three Northern Hemisphere peatlands from Yellowknife (NWCanada), Abisko (N Sweden), and the Northern Ural Mountains (NWRussia). Sphagnum riparium macrofossils were present in transitional phases between rich fen and oligotrophic bog. Sphagnum riparium was a dominant species in the three sites and was found in combination with Sphagnum angustifolium , Drepanocladus sp., and vascular plants including Andromeda polifolia , Chamedaphne calyculata and Oxycoccus palustris . Testate amoebae indicate that the species occurred in wet to moderately wet conditions (water-table depth inferred from a testate amoeba transfer function model ranged between 25 and 0 cm under the peatland surface). The wet-indicator taxa Archerella flavum and Hyalosphenia papilio dominated the testate amoeba communities in peat horizons containing Sphagnum riparium . The presence of Sphagnum riparium macrofossils in peat profiles in the Northern Hemisphere can be interpreted as an indication of wet minerotrophic conditions, often corresponding to a rise in water-level and establishment of a wet habitat. Sphagnum riparium is a transient species in these peatlands and is replaced by communities dominated by more acidophilic species such as Sphagnum angustifolium , Sphagnum russowii , and Sphagnum fuscum . Our data show that although Sphagnum riparium is a transient peat-forming species, it is widespread in sub-arctic and boreal environments. The subfossil occurrence of Sphagnum riparium in the Northern Hemisphere may indicate that its range has increased during the Late Holocene. The conservation of Sphagnum riparium in peatlands depends on the existence of relatively short-lived transitional communities which potentially can be artificially created.